2011
DOI: 10.1007/s00268-010-0939-9
|View full text |Cite
|
Sign up to set email alerts
|

The Hypofunctional Effect of P335L Single Nucleotide Polymorphism on SSTR5 Function

Abstract: Introduction Somatostatin receptor subtype 5 (SSTR5) mediates the inhibitory effect of somatostatin on insulin expression/secretion and cell proliferation. A number of single nucleotide polymorphisms (SNPs) of SSTR5 have been identified, including P335L, a non-synonymous SNP located in the protein C-terminal region and encrypted by the codons CCG (proline) or CTG (leucine). In the present study, we sought to determine if the P335L SNP affected the cellular function of SSTR5 in human pancreatic cancer as has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…The evidence includes: 1) metformin inhibited PDX-1 transactivity; 2) metformin reduced PDX-1 protein and mRNA levels; and 3) metformin abrogated the increase in PDX-1 expression induced by EGF, a potent growth factor for PDAC cells. In pancreatic β cells, PDX-1 expression is subject to positive regulation by glucose, glucagon-like pepetide (GLP-1) [36, 37] and palmitic acid [38] as well as negative regulation by DNA damage [39], oxidative stress [40], somatostatin receptor 5 (SSTR5) agonist PRL-1980 [41] and advanced glycation end-products (AGEs) [42] via different mechanisms. It is not known whether these signals also operate in PDAC cells where PDX-1 acts as a pro-oncogenic transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence includes: 1) metformin inhibited PDX-1 transactivity; 2) metformin reduced PDX-1 protein and mRNA levels; and 3) metformin abrogated the increase in PDX-1 expression induced by EGF, a potent growth factor for PDAC cells. In pancreatic β cells, PDX-1 expression is subject to positive regulation by glucose, glucagon-like pepetide (GLP-1) [36, 37] and palmitic acid [38] as well as negative regulation by DNA damage [39], oxidative stress [40], somatostatin receptor 5 (SSTR5) agonist PRL-1980 [41] and advanced glycation end-products (AGEs) [42] via different mechanisms. It is not known whether these signals also operate in PDAC cells where PDX-1 acts as a pro-oncogenic transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, SSTR5 P335L SNP results from a C to T change at the 1004 th nucleotide of the human SSTR5 gene. It has been shown that SSTR5 P335L SNP is associated with neuropsychiatric diseases [11,12], pituitary adenomas [13] and pancreatic cancer [14,15]. Our recent studies also show that SSTR5 P335L is a hypofunctional SNP and, thus, could have a harmful effect on the normal functions of SSTR5 [15].…”
Section: Introductionmentioning
confidence: 73%
“…The hypofunctional property of SSTR5 P335L SNP [15] and its association with human diseases [1114] strongly suggest that SSTR5 P335L is a potential biomarker for these human diseases. Therefore, we generated an anti-SSTR5 P335L mAb that shows specificity to SSTR5 P335L, but not WT SSTR5, overexpressed in HEK293 cells [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, such diagnostics allow for the down-selection of the most efficacious, safest treatments prior to testing on animal models. Unfortunately, most of these in vitro evaluations are performed using cells seeded onto standard tissue culture plastic (TCP) [1][2][3][4] or biologically functionalized or coated TCP. 5,6 Though 2D studies can provide useful information, these substrates lack physical homology with the native extracellular matrix, which can alter cell behavior and reduce the ability to translate laboratory findings to the clinic.…”
mentioning
confidence: 99%